MAKNA TRADISI TARIAN ADAT BONET PADA MASYARAKAT ATONI PAH METO DI KABUPATEN TIMOR TENGAH SELATAN - Kesya Igelda Missa; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Indonesia is known as a cauntry rich in cultural diversity, one of which is reflected in traditional dances that express the identity and values of its people. This study discusses the Bonet Dance as a cultural heritage of the Dawan Tribe (Atoni Pah Meto) in East Nusa Tenggara. Using a descriptive quantitative approach through library research, this study aims to reveal the social, spiritual, and cultural meanings contained within the Bonet tradition. The findings show that the Bonet Dance is not merely a performing art but a medium of cultural communication that embodies symbols of togetherness, equality, and cosmic harmony. Each element of the dance such as circular movements, handholding formations, chants, and accompaniment reflectd values of solidarity, respect for ancestors, and balance between humans, nature, and divine forces. In addition to serving as entertainment and a ritual performance, Bonet also has educational and instilling the value of mutual cooperation. In the modern era, Bonet remains relevant as a guardian of the Dawan Tribe’s cultural identity, local wisdom, and the continuity of the cultural values of the Timorese people.